Effects of combined resisted sprint training with small-sided games compared to regular soccer training on physical performance in professional soccer players - Sal-de-Rellán, A.; Ben Brahim, M.; Martín, V.; Yassin, H.; Sánchez-Sánchez, J. (International Journal of Sports Science and Coaching, 2025)
The aim of our study was to compare the effects of combining small-sided games training with resisted sprint training in relation to regular soccer training on soccer players` physical performance. Twenty-seven male soccer players (age: 21.22 ± 1.18 years; height: 1.79 ± 0.05 m; body mass: 73.91 ± 4.83 kg) were randomly assigned to an experimental group (EG, n = 16) or a control group (CG, n = 11). The intervention program had to be performed 2 times a week over 6 weeks. The only difference between the 2 groups was that the EG performed a combined training using small-sided games and resisted sprints, while the CG performed the regular soccer training. Within-group analysis showed significant improvements in 5 meters (5-m), countermovement jump (CMJ), squat jump (SJ), mean time (RSAm) and the percentage of decrement (%Dec) from pretest to posttest in EG. However, CG did not show significant improvements in any performance variable. Between-groups analysis revealed differences in favor of the EG in CMJ and SJ. In conclusion, the results of this study indicate that combined SSG + RST training will improve the performance of soccer players (acceleration, jumping and RSA). In practical terms, strength and conditioning coaches should consider including this programme as over a short period of 6 weeks (2 times per week) for 30 min it has been effective in improving the performance of soccer players.